KARAKTERISTIK KEPENULISAN DAN KARAKTERISTIK ARTIKEL PADA JURNAL PSIKOLOGI UNIVERSITAS GADJAH MADA: KAJIAN BIBLIOMETRI - Irianti, Pergola (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2017)
The purpose of this study is to know how the characteristics of authorship, authors involvement, and characteristics of the articles in the Jurnal Psikologi UGM 1976-2015 period. In this descriptive quantitative study, data were collected by documentation method. Jurnal Psikologi UGM is research subject, and all of article in the journal is unit analysis. Data were collected by documentation method while the data were analyze by the percentage formula and presented by table of frequency. As many as 53 numbers of Journal of Psychology UGM were collected. The results showed percentage of women author are (60,12%) higher than men. Most of them are lecturer (52,95%) and college students (35,30%), from the Faculty of Psychology Universitas Gadjah Mada (62,30%) and the other (37,70%). Education level of writer, post graduate (80%) higher than bachelor (20%). Joint authorship (56,88%) are higher than single authorship (43,11%), with the collaboration level of 0,56. Highest frequency the involvement of the authors is Faturochman as many as 16 articles. Most articles use Indonesian language (92,96%), and the rest in English. Long of article between 11-15 pages (41,9%) highest. Based on subject, Clinical and Counseling Psychology (25,5%) highest, and then Social Psychology (25,1%), Educational Psychology and Psychometrics (24,5%). Based on research methods of article, 67,22% articles using quantitative survey methods.